Association between Psychological Aspects and Coping Strategies among Mothers of Children with Cancer - Hind Tasjeel Abass Alfatlawy; Salma K. Jihad (Kufa Journal for Nursing Sciences)
Background: Providing care for a child diagnosed with cancer presents significant emotional and psychological difficulties for parents, especially mothers.